Clinical and laboratory profile of patients with sickle cell anemia - Sant'Ana,Phelipe Gabriel dos Santos (2017)
Abstract Objective: This study aimed to describe and analyze clinical and laboratory characteristics of patients with sickle cell anemia treated at the Hemominas Foundation, in Divinópolis, Brazil. Furthermore, this study aimed to compare the clinical and laboratory outcomes of the group of patients treated with hydroxyurea with those patients that were not treated with hydroxyurea. Methods: Clinical and laboratorial data were obtained by analyzing medical records of patients with sickle cell anemia. Results: Data from the medical records of 50 patients were analyzed. Most of the patients were female (56%), aged between 20 and 29 years old. Infections, transfusions, cholecystectomy, splenectomy and systemic arterial hypertension were the most common clinical adverse events of the patients. The most frequent cause of hospitalization was painful crisis. The majority of patients had reduced values of hemoglobin and hematocrit (8.55 ± 1.33 g/dL and 25.7 ± 4.4%, respectively) and increased fetal hemoglobin levels (12 ± 7%). None of the clinical variables was statistically significant on comparing the two groups of patients. Among hematological variables only hemoglobin and hematocrit levels were statistically different between patients treated with hydroxyurea and untreated patients (p-value = 0.005 and p-value = 0.001, respectively). Conclusion: Sickle cell anemia requires treatment and follow-up by a multiprofessional team. A current therapeutic option is hydroxyurea. This drug reduces complications and improves laboratorial parameters of patients. In this study, the use of the drug increased the hemoglobin and hematocrit levels of patients.